The effect of music to sleep quality on liver transplanted patients (Annals of Medical Research, 2025)
Aim: This study aimed to evaluate the effect of music listening on sleep quality in adult liver transplant recipients. Given the limited research in this specific patient population, the study contributes to the growing body of evidence supporting non-pharmacological strategies in postoperative nursing care.Materials and Methods: A quasi-experimental pre-test/post-test control group design was employed. A total of 88 patients were included, with 44 assigned to the experimental group and 44 to the control group. Sleep quality was assessed using the Richards-Campbell Sleep Questionnaire (RCSQ) before and after the intervention. The experimental group listened to 30 minutes of culturally familiar music each night for four consecutive days, while the control group received standard care only.Results: Baseline RCSQ scores indicated poor sleep quality in both groups. Following the intervention, the experimental group showed a statistically significant improvement in total RCSQ scores (from 24.0 to 50.0, p < 0.001). Subscale analysis revealed significant improvements in all five RCSQ dimensions—sleep depth, sleep latency, frequency of nighttime awakenings, wake time, and overall sleep quality (p < 0.001). In contrast, the control group showed no meaningful change except for a slight improvement in the frequency of awakenings subscale (p = 0.035).Conclusion: These findings suggest that music listening can significantly enhance sleep quality in liver transplant recipients. As a safe, inexpensive, and easy-to-apply method, music listening holds promise for integration into routine postoperative nursing care to promote patient comfort and recovery.
Keywords: Liver transplantation; Music; Sleep quality; Postoperative care; Nursing intervention; Richards-Campbell Sleep Questionnaire